Cluster randomised controlled trial of 'whole school' child maltreatment prevention programme in primary schools in Northern Ireland: study protocol for Keeping Safe - Aisling McElearney; Aoibheann Brennan-Wilson; Christina Murphy; Phyllis Stephenson; Brendan Bunting (BMC, 2018)
Abstract Background Child maltreatment has a pervasive, detrimental impact on children's wellbeing. Despite a growing focus on prevention through school based education, few programmes adopt a whole- school approach, are multi-component, seek to address all forms of maltreatment, or indeed have been robustly evaluated. This paper describes a cluster randomised controlled trial designed to evaluate a school based child maltreatment prevention programme: 'Keeping Safe' in primary schools in Northern Ireland. The intervention has been designed by a non-profit agency. Programme resources include 63 lessons taught incrementally to children between four and 11 years old, and is premised on three core themes: healthy relationships, my body, and being safe. There are programme resources to engage parents and to build the capacity and skills of school staff. Methods/design A cluster Randomised Controlled Trial (RCT) will be conducted with children in 80 schools over a two-year period. The unit of randomisation is the school. Schools will be allocated to intervention or wait-list control groups using a computer-generated list. Data will be collected at three time points: baseline, end of year one, and end of year two of programme implementation. Primary outcomes will include: children's understanding of key programme concepts, self-efficacy to keep safe in situations of maltreatment, anxiety arising from programme participation, and disclosure of maltreatment. Secondary outcomes include teachers' comfort and confidence in teaching the programme and parents' confidence in talking to their children about programme concepts. Discussion This RCT will address gaps in current practice and evidence regarding school based child maltreatment prevention programmes. This includes the use of a whole- school approach and multi-component programme that addresses all maltreatment concepts, a two-year period of programme implementation, and the tracking of outcomes for children, parents, and teachers. Methodologically, it will extend our understanding and learning in: capturing sensitive outcome data from young children, adapting and using standardised measures with children of different ages, the use of school level administrative data on staff reports/children's disclosure of maltreatment as behavioural outcomes, and the conduct of complex trials within the busy school environment. Trial registration ClinicalTrials.gov: NCT02961010 (Retrospectively registered 8 November 2016).